The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1103/physrevd.91.123539
|View full text |Cite
|
Sign up to set email alerts
|

Interaction in the dark sector

Abstract: It may well happen that the two main components of the dark sector of the Universe, dark matter and dark energy, do not evolve separately but interact nongravitationally with one another. However, given our current lack of knowledge on the microscopic nature of these two components there is no clear theoretical path to determine their interaction. Yet, over the years, phenomenological interaction terms have been proposed on mathematical simplicity and heuristic arguments. In this paper, based on the likely evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 41 publications
3
55
0
Order By: Relevance
“…[34] that an interaction proportional to Hρ x could be consistent with the second law of thermodynamics if the energy transfer is from DE to DM, also, in Ref. [35] it was shown that interactions proportional to H (ρ m + ρ x ) or Hρ m can arise by imposing simple thermodynamic arguments based on the evolution of the ratio ρ m /ρ x . For interactions proportional to ρ m , ρ x or a linear combination of both, we note from Eqs.…”
Section: Interacting Modelsmentioning
confidence: 99%
“…[34] that an interaction proportional to Hρ x could be consistent with the second law of thermodynamics if the energy transfer is from DE to DM, also, in Ref. [35] it was shown that interactions proportional to H (ρ m + ρ x ) or Hρ m can arise by imposing simple thermodynamic arguments based on the evolution of the ratio ρ m /ρ x . For interactions proportional to ρ m , ρ x or a linear combination of both, we note from Eqs.…”
Section: Interacting Modelsmentioning
confidence: 99%
“…The dynamical nature of dark energy also introduces a new cosmological problem, namely, "coincidence" problem [26]. One alternative to the coincidence problem are coupled dark energy models where DE interchanges energy with the dark matter (DM) by means of a coupling term [27][28][29][30][31][32]. Though a number of theoretical models have been proposed, none of them provides a satisfactory solution to all the problems.…”
Section: Introductionmentioning
confidence: 99%
“…In [46], the authors define the ratio between CDM and DE energy densities ρ m /ρ e in a FLRW homogeneous model. For an interacting term proportional to the DE energy density, they show that the ratio is positive defined, and decreases from infinity monotonously as the universes expands.…”
Section: Homogeneous Subspacementioning
confidence: 99%